Karakteristik dan Model Bimbingan Pendidikan Islam ABK Tuna Laras - Agustina, Silfiya; Salma, Hanifah; Rifki, Moh (TSAQOFAH, 2022)
Humans are created with various potentials that exist within themselves. Humans have a unique diversity and all humans are perfect in their own way. This does not mean that someone who has a handicap or disorder is an imperfect human being. In everyday life, people with special needs have the same rights as other humans. Characteristics and types of special needs are different, one of which is social and emotional behavior disorders. By reviewing more deeply the characteristics of children with special needs (ABK) with mental retardation, so that they are able to give more attention to them. Based on the literature, it can be interpreted that not all naughty children are evil. Before giving them a negative label, they should be able to identify what makes their behavior different from the others. The provision of services and guidance on a regular basis both in the school, home, and community environment will further direct the mentally retarded crew to be better. One of the guidance models in this mentally retarded ABK is to provide Islamic education and inclusive education so that they can return to real human nature.